Mild and site-selective nucleophilic C-H functionalization of pyridines via its stable N-alkylated salts - Baral, Nilofar; Saikia, Pinku; Molla, Sabir Ali; Dewangan, Devendra Kumar; Maity, Pradip (Journal of the American Chemical Society, 2026)
Direct, site-selective C-H functionalization of pyridines offers an efficient approach to both streamlined synthesis and late-stage modification of bioactive and functional molecules. Existing approaches to direct nucleophilic substitution typically rely on highly reactive nitrogen-activating groups, which limit nucleophile scope and functional group tolerance and often suffer from poor site selectivity. Although milder activating groups address some of these limitations, they generally require additional installation and removal steps. Herein, we report a mild and general strategy employing designed alkyl halide activators that enables one-pot, site-selective functionalization of pyridines with synthetically valuable yet challenging nucleophiles. This strategy allows, for the first time, direct pyridine functionalization with a broad range of phosphites and amines, in addition to methoxide and cyanide. The mild and redox-neutral reaction conditions are particularly well suited for late-stage functionalization (LSF) of pharmaceutically relevant molecules, enabling site-selective modification with both phosphites and amines. The rational design of the alkyl halide activators, together with careful analysis of side-product formation, reveals the delicate balance required for success with electronically diverse nucleophiles and suggests broader applicability of this C-H functionalization strategy.